WORK-LIFE BALANCE OF JEMBER UNIVERSITY LECTURERS - Ainul Qismatil Katsiiroh; Anita Dewi Prahastuti Sujoso (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Work-life balance is a condition that occurs when the demands of work and the demands of personal life are balanced. Previous research stated that work-life balance for lecturers was achieved during the Work-from-Home (WFH) or online learning. However, it is known that the current learning system has returned to the offline system. Purpose: The purpose of the research was to determine factors of work-life balance among Jember University lecturers. Method: This type of research is observational analytics using a cross-sectional research design. The instrument used in the research was a work-life balance questionnaire developed by Fisher. The population for this research was 376 Jember University lecturers who were actively teaching. 128 respondents were taken as the sample. Sample selection in the research used a proportional random sampling technique and used the contingency coefficient and Chi-square statistical test. Result: The results showed that most respondents were male (54.7%), aged 28 to 46 years (64.1%), married (91.4%), had ≤2 children (62.5%), had functional positions of lectors (35.2%), had no structural positions (59.4%), and had no side jobs (68.8%). There was no significant relationship between sex (0.252), age (0.502), marital status (0.682), number of children (0.145), functional positions (0.312), structural positions (0.509), and side jobs (0.094) with work-life balance. Conclusion: Demographic and job characteristics do not affect the work-life balance among lecturers at University of Jember.